Systematic review of the epidemiological evidence of associations between quantified occupational exposure to respirable crystalline silica and the risk of silicosis and lung cancer - Mundt, Kenneth A.; Thompson, William J.; Dhawan, Gaurav; Checkoway, Harvey; Boffetta, Paolo (Frontiers in Public Health, 2025)
IntroductionOccupational exposure to respirable crystalline silica (RCS) has been associated with both silicosis and lung cancer, but no systematic review (SR) specifically focused on exposure-response relationships has been published for these diseases.MethodsWe conducted this SR in compliance with Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. PubMed searches, supplemented with Web of Science and Google Scholar searches, identified 1,007 potentially relevant articles. After applying selection criteria and removing duplicates, 65 publications were reviewed and evaluated, 20 of which presented at least semi-quantitative exposure-response results for lung cancer (n = 12) and/or silicosis (n = 10).ResultsCumulative RCS exposure was most commonly reported. Increasing silicosis risk with increasing cumulative RCS exposure was reported in all studies, with exposure thresholds indicated, but at different cumulative exposures. For most studies defining silicosis as International Labor Organization (ILO) score ≥ 1/0, substantially increased risks were clear at or above 1 mg-/m3-yr. For lung cancer, exposure-response estimates were mixed with 4 studies reporting no statistically significantly increased relative risk of lung cancer at any cumulative RCS exposure. Three studies reported statistically significant increased risks but only for high cumulative RCS exposures. Residual confounding by smoking was not explicitly discussed in most studies. One case–control study presented an exposure-response analysis for silica and lung cancer limited to never-smokers with substantial silica exposure; risk was increased only among those in the highest RCS exposure category. Studies with more detailed smoking information generally reported risks close to background levels except at the highest cumulative RCS exposure categories.ConclusionSilicosis risk clearly and consistently was increased above cumulative exposure thresholds of roughly 1 mg/m3-years across most studies. However, for lung cancer, results were heterogeneous with potential residual confounding by smoking complicating interpretation. Results suggest that lung cancer risk may not be increased at cumulative RCS exposures below the reported exposure thresholds for silicosis risk.